Instant 99mTc Compounds - Eckelman, W. C.; Richards, P. (Nuklearmedizin - NuclearMedicine, 1971)
The full potential use of technetium has not been achieved despite its ideal physical properties, dosimetry and availability because of the complex preparations required for 99mTc radiopharmaceuticals. One of the goals of our work is to develop techniques for the preparation of high-purity 99mTc compounds which can be easily prepared, ideally by adding pertechnetate to a prepared solution.The use of stannous ion as reducing agent for technetium makes it possible to obtain such one-step, high-purity products. All non-radioactive components can be premixed in a single vial before addition of the radioactive pertechnetate. No final pH adjustment, further chemical manipulation or purification is required.Procedures for two instantly labeled compounds have been developed to date: 99mTc DTPA and 99mTc HSA. The 99mTc DTPA is prepared by adding pertechnetate to a previously prepared solution of stannous ion and CaNa3 DTPA which has been stored at pH 4. The 99mTc HSA is prepared by adding pertechnetate to a solution of stannous ion and HSA. The parametric variations and analytical techniques involved in formulating these procedures are described. It appears that development of kits for other biologically interesting compounds may be possible using similar procedures.